Baseline hydrocarbon levels in New Zealand coastal and marine avifauna. Issue 1 (15th May 2015) - McConnell, H.M.; Gartrell, B.D.; Chilvers, B.L.; Finlayson, S.T.; Bridgen, P.C.E.; Morgan, K.J.
Highlights: Hydrocarbon fractions such as polycyclic aromatic hydrocarbons (PAHs) can cause wildlife poisoning. Baseline PAH values are needed to differentiate between background levels and PAH exposure due to an oil spill. This study investigated the baseline levels for 22 PAHs in New Zealand avian wildlife. Overall, concentrations were low, with variation linked to species foraging habitat and migratory patterns. Abstract: The external effects of oil on wildlife can be obvious and acute. Internal effects are more difficult to detect and can occur without any external signs. To quantify internal effects from oil ingestion by wildlife during an oil spill, baseline levels of ubiquitous hydrocarbon fractions, like polycyclic aromatic hydrocarbons (PAHs), need to be established. With these baseline values the extent of impact from exposure during a spill can be determined. This research represents the first investigation of baseline levels for 22 PAHs in New Zealand coastal and marine avian wildlife. Eighty-five liver samples were tested from 18 species. PAHs were identified in 98% of livers sampled with concentrations ranging from 0 to 1341.6 ng/g lipid wt or on wet wt basis, 0 to 29.5 ng/g. Overall, concentrations were low relative to other globally reported avian values. PAH concentration variability was linked with species foraging habitat and migratory patterns.